Detection of Staphylococcus aureus and Staphylococcus epidermidis in Clinical Samples by 16S rRNA-Directed In Situ Hybridization - Krimmer, Vanessa (American Society for Microbiology, 1999)
Staphylococcus epidermidis and Staphylococcus aureus are the most common causes of medical device-associated infections, including septicemic loosenings of orthopedic implants. Frequently, the microbiological diagnosis of these infections remains ambiguous, since at least some staphylococci have the capacity to reduce their growth rate considerably. These strains exhibit a small-colony phenotype, and often they are not detectable by conventional microbiological techniques. Moreover, clinical isolates of S. aureus and S. epidermidis adhere to polymer and metal surfaces by the generation of thick, multilayered biofilms consisting of bacteria and extracellular polysaccharides. This study reports improved detection and identification of S. aureus and S. epidermidis by an in situ hybridization method with fluorescence-labeled oligonucleotide probes specific for staphylococcal 16S rRNA. The technique has proven to be suitable for the in situ detection of staphylococci, which is illustrated by the identification of S. epidermidis in a connective tissue sample obtained from a patient with septicemic loosening of a hip arthroplasty. We also show that this technique allows the detection of intracellularly persisting bacteria, including small-colony variants of S. aureus, and the differentiation of S. epidermidis from other clinically relevant staphylococci even when they are embedded in biofilms. These results suggest that the 16S rRNA in situ hybridization technique could represent a powerful diagnostic tool for the detection and differentiation of many other fastidious microorganisms.